Crisis y fractura del sistema productivo local de Cuitzeo - Alejo Moreno, Alma Liliana (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
This paper seeks to reflect on the problems facing the municipality of Cuitzeo which are directly related to the generation and evolution of their local system. The elements that have led to the current crisis in the local production system are analyzed. The paper has taken into account the interrelationships established with the economic, social and environmental dimensions that comprise it. Cuitzeo was for many years a town that enjoyed a solvent and progressive economic situation, which over the years, and due to the processes analyzed here as paternalism, migration and a trend towards individual work, led the municipality to a long crisis situation without a perspective for a solution, which we characterize as fracture of the local production system and which has deteriorated the quality of life of its inhabitants. The most important process to understand this situation is the decreased levels of consistency of social capital in the municipality, question addressed in this study, especially evident in its economic consequences. An assessment of the prospects for the Municipality, as well as reflections to establish points that can guide the work of local development in Cuitzeo, is presented.

El presente trabajo busca reflexionar acerca de la problemática que atraviesa el Municipio de Cuitzeo, que tiene que ver directamente con la generación y evolución de su sistema local. Se analizan los elementos que han conducido a la situación actual de crisis del sistema productivo local. Se ha tomado en cuenta las interrelaciones que establece con las dimensiones económica, social y ambiental, que lo conforman. Cuitzeo fue durante muchos años una localidad que gozó de un situación económica solvente y progresiva, que con el paso de los años, y a raíz de los procesos que analizamos, como el paternalismo, la emigración y tendencia al trabajo individual llevaron al Municipio a una situación de crisis larga sin perspectivas de solución, que caracterizamos como fractura del sistema productivo local, y que ha deteriorado la calidad de vida de sus habitantes. El proceso más importante para comprender esta situación es la disminución de los niveles de consistencia de capital social del Municipio, cuestión que se aborda en el presente estudio, manifiesto especialmente en sus consecuencias económicas. Se presenta también un balance de las perspectivas que tiene el Municipio, así como reflexiones para establecer puntos que puedan orientar el trabajo de desarrollo local en Cuitzeo.
Facultad de Economía Vasco de Quiroga. Maestría en Ciencias en Desarrollo Local
Keywords: info:eu-repo/classification/cti/5; FEVAQ-M-2015-0280; Crisis económica; Paternalismo; Emigración; Capital social; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4990